Towards attractive texture modified foods with increased fiber content for dysphagia via 3D printing and 3D scanning - Ahlinder, Astrid; Höglund, Evelina; Öhgren, Camilla; Miljkovic, Ana; Stading, Mats (Frontiers in Food Science and Technology, 2023)
As life expectancy increases so do age related problems such as swallowing disorders, dysphagia, which affects 10%–30% of people over 65 years old. For dysphagia patients the texture and rheological properties of the food, and the bolus, is critical to avoid choking and pneumonia. Texture modified foods, timbals, are often served to these patients due to their ease of swallowing. The main concern with these foods is that they do not look visually alike the food they replace, which can decrease the patient’s appetite and lead to reduced food intake and frailty. This study aims to improve both the visual appearance of texturized food as well as the energy density and fiber content of the timbal formulation. 3D scanning and additive manufacturing (3D Printing) were used to produce meals more reminiscent of original food items, increasing their visual appeal. Rheology was used to ensure the original flow profile was maintained as the timbal was reformulated by reducing starch contents and partially replacing with dietary fibers. The amount of starch was reduced from 8.7 wt% in the original formulation to 3.5 wt% and partially replaced with 3 wt% citrus fiber, while maintaining properties suitable for both swallowing and 3D printing. The resulting formulation has improved nutritional properties, while remaining suitable for constructing visually appealing meals, as demonstrated by 3Dprinting a chicken drumstick from a model generated with 3D scanning.